A Review on the Fascinating World of Insect Resources: Reason for Thoughts - R. K. Lokeshwari; T. Shantibala (Psyche: A Journal of Entomology)
Insect resources are vast and diverse due to their enormous diversity. The exploitation and utilization of insect resources is broadly classified into four different categories. The first category is the insects of industrial resources. This level includes the utilization of silk worm, honeybee, lac insect, dye insect, and aesthetic insect. The second category is the utilization of insects for edible and therapeutic purposes. Insects are high in protein and many are rich sources of vitamins and minerals. The third category is the use of insects in forensic investigation. By analyzing the stages of succession of insects at first, rough estimation of the postmortem intervals can be done. The fourth category is the insects of ecological importance. Many insect species act as potential predators and parasites of destructive pests of insect order Lepidoptera, Diptera, and Orthoptera. Insects are also used as bioindicator to assess the cumulative effects of environmental stressors such as pollutants. Despites these fascinating benefits, insect resources are often neglected in India due to lack of proper documentation, less expertise, and advance enterprises in these fields. Hence, the paper reviews the different fascinating facets of insect resources in order to explore and utilize it in a sustainable way with reference to Indian region.